Beamformer Sensitivity to Microphone Manufacturing Tolerances - Tashev, Ivan (Proc. of the Nineteenth Int. Conference Systems for Automation of Engineering and Research (SAER), 2005)
One of the major problems in achieving and assuring the estimated parameters of microphone arrays during mass production is the mismatch between capturing channels, caused primarily by the variations in the manufacturing tolerances of the microphones that are used. This paper presents a methodology and the results of sensitivity analysis of beamformer parameters to these variations. A Monte Carlo method is used to simulate the mismatch in microphone responses. The beamformer noise gain and directivity index are used for evaluation. The results of the analysis justify taking measures to ensure channel matching by selecting microphones with close parameters, or by calibrating the microphones. This paper presents the requirements for microphone selection and calibration.